New York World's Fair 1939 - Scene looking towards Railroad Building (Miller Art Company)
Pictured here is the Bridge of Wheels looking towards the Railroad Building, the largest exhibit structure on the grounds. The Bridge crosses Grand Central Parkway Extension and connects the Transportation Area with the Communications and Business Systems Zone